Safety and efficacy of upfront plerixafor + G‐CSF versus placebo + G‐CSF for mobilization of CD34+ hematopoietic progenitor cells in patients ≥60 and <60 years of age with non‐Hodgkin's lymphoma or multiple myeloma. Issue 12 (9th September 2013) - Micallef, Ivana N.; Stiff, Patrick J.; Stadtmauer, Edward A.; Bolwell, Brian J.; Nademanee, Auayporn P.; Maziarz, Richard T.; Partisano, Angela M.; Marulkar, Sachin; DiPersio, John F.
Abstract : The efficacy and safety of plerixafor + G‐CSF in enhancing hematopoietic stem cell mobilization and collection has been demonstrated in two phase III studies involving patients with NHL or MM. In these pivotal studies, plerixafor + G‐CSF significantly increased the proportion of patients achieving target stem cell yields, compared to placebo + G‐CSF. In this analysis, we compare the efficacy and safety of plerixafor + G‐CSF versus placebo + G‐CSF in patients enrolled in the two phase III studies, stratified by age: ≥60 years of age and <60 years of age. The proportion of older patients who achieved target stem cell yields was significantly higher in the plerixafor group than in placebo group (NHL: 50.9 vs. 25.4%, P < 0.001; MM: 69.6 vs. 23.7%, P < 0.001). In this older cohort, the median times to neutrophil and to platelet engraftment following autologous stem cell transplant were comparable between the plerixafor and placebo groups. Similar efficacy findings were observed in the younger age group. The most common adverse events (all grades) reported among older patients in the plerixafor group included diarrhea (41.3%), nausea (38.9%), fatigue (30.2%), and injection‐site reaction (29.4%). The frequency of adverse events was similar between the older and the younger age groups. Taken together, our subanalysis demonstrate that plerixafor + G‐CSF can be safely and effectively used in adult patients of all ages, including those ≥60 years, to support optimal stem cell mobilization for autologous stem cell transplantation. Am. J. Hematol. 88:1017–1023, 2013. © 2013 Wiley Periodicals, Inc.